1994
DOI: 10.1007/s001250050152
|View full text |Cite
|
Sign up to set email alerts
|

Fetal growth and insulin secretion in adult life

Abstract: Summary Recent studies suggest that NIDDMislinked with reduced fetal and infant growth. Observations on malnourished infants and studies of experimental animals exposed to protein energy or protein deficiency in fetal or early neonatal life suggest that the basis of this link could lie in the detrimental effects of poor early nutrition on the development of the beta cells of the islets of Langerhans. To test this hypothesis we have measured insulin secretion following an IVGTT in a sample of 82 normoglycaemic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 10 publications
1
21
0
Order By: Relevance
“…People who are small for gestational age may therefore have only insulin resistance, with no defects in insulin secretion. This hypothesis is supported by the results of the insulin response to the intravenous glucose tolerance test, which did not correlate with birth weight or ponderal index at birth 29 30 31…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…People who are small for gestational age may therefore have only insulin resistance, with no defects in insulin secretion. This hypothesis is supported by the results of the insulin response to the intravenous glucose tolerance test, which did not correlate with birth weight or ponderal index at birth 29 30 31…”
Section: Discussionmentioning
confidence: 89%
“…More recently a study of 1333 men aged 50-60 who were born and living in Uppsala confirmed that reduced fetal growth is associated with insulin resistance and non-insulin dependent diabetes mellitus and suggested a specific association with thinness at birth 29. This relation seems to be mediated through insulin resistance rather than through ß cell dysfunction 29 30 31…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, if the restricted diet continues into adulthood, no metabolic changes are observed and pathologies associated with chronic diseases are prevented (40). Similarly in humans, fetal growth restriction has been shown to impact insulin action in adulthood (41). Data obtained from epidemiological studies have shown that subjects who had low birth weight or were thin at birth have a higher prevalence of developing insulin resistance syndrome or syndrome X in adulthood, accompanied by the co-existence of glucose intolerance, hypertension and hypertriglyceridemia (35,36,38,42,43).…”
Section: Discussionmentioning
confidence: 96%
“…To explain the association between reduced fetal growth and glucose intolerance the Cambridge-Southampton group initially suggested that inadequate fetal nutrition might impair the development of the endocrine pancreas 1 2 3. This is not consistent with the lack of association between birth weight and acute insulin response to intravenous glucose challenge in Uppsala and in an earlier study of men and women born in Preston 4. In the Preston study insulin resistance was inversely related to ponderal index but not to birth weight5; this led the investigators to suggest that the association between reduced fetal growth and glucose intolerance is mediated through insulin resistance.…”
Section: Discussionmentioning
confidence: 98%
“…Initially it was suggested that the relation between reduced fetal growth and glucose intolerance was mediated through impairment of β cell function 1 3. More recent work has led the same investigators to suggest instead that the association is mediated through insulin resistance 4 5. The objective of our study was to distinguish between these two possible mechanisms.…”
Section: Introductionmentioning
confidence: 92%